The Relationship of Knowledge and Attitude with The Implementation of Health Protocol on Fishers at The Fish Auction Place (TPI) River Padang, Medang Deras District - Bangun, Sri Melda Br (Universitas Aisyah Pringsewu, 2020)
The implementation of the health protocol is wearing a mask, washing hands and keeping a distance. rules or regulations that must be followed from all parties in order to be able to carry out activities safely during the pandemic. This study uses quantitative research methods that are analytical surveys using cross-sectional. Samples were taken as many as 50 fishermen at TPI Sungai Padang from 50 populations with a sampling technique using total sampling. The purpose of this study was to determine the relationship between knowledge and attitudes with the implementation of health protocols for fishermen at the Padang River Fish Auction Place (TPI) in the district of Medang swift, Batu Bata district in 2020. Data analysis was used with chi-square with =0.05. the results of the bivariate study showed that there was a relationship between knowledge of 0,010 less than 0.05. Then there is a relationship between attitudes and the implementation of health protocols, the result of which the P Value is 0,002 less than 0.05.